2020
DOI: 10.1609/aaai.v34i05.6402
|View full text |Cite
|
Sign up to set email alerts
|

SensEmBERT: Context-Enhanced Sense Embeddings for Multilingual Word Sense Disambiguation

Abstract: Contextual representations of words derived by neural language models have proven to effectively encode the subtle distinctions that might occur between different meanings of the same word. However, these representations are not tied to a semantic network, hence they leave the word meanings implicit and thereby neglect the information that can be derived from the knowledge base itself. In this paper, we propose SensEmBERT, a knowledge-based approach that brings together the expressive power of language modelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 27 publications
(42 reference statements)
0
74
0
Order By: Relevance
“…Besides deep learning-based approach, Loureiro and Jorge (2019) and Scarlini et al (2020) construct sense embeddings using the contextual embeddings from BERT. The former generates sense embeddings by averaging the contextual embeddings of sense-annotated tokens taken from Sem-Cor while the latter constructs sense embeddings by concatenating the contextual embeddings of Ba-belNet definitions with the contextual embeddings of Wikipedia contexts.…”
Section: Feature-based Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides deep learning-based approach, Loureiro and Jorge (2019) and Scarlini et al (2020) construct sense embeddings using the contextual embeddings from BERT. The former generates sense embeddings by averaging the contextual embeddings of sense-annotated tokens taken from Sem-Cor while the latter constructs sense embeddings by concatenating the contextual embeddings of Ba-belNet definitions with the contextual embeddings of Wikipedia contexts.…”
Section: Feature-based Approachesmentioning
confidence: 99%
“…The former generates sense embeddings by averaging the contextual embeddings of sense-annotated tokens taken from Sem-Cor while the latter constructs sense embeddings by concatenating the contextual embeddings of Ba-belNet definitions with the contextual embeddings of Wikipedia contexts. For WSD, both approaches make use of the constructed sense embeddings in nearest neighbor classification (kNN), in which the simple 1-nearest neighbor approach from Scarlini et al (2020) showed substantial improvement over the nominal category of the English all-words WSD benchmark datasets.…”
Section: Feature-based Approachesmentioning
confidence: 99%
“…A further step towards semantic representations involves modelling individual word senses as vectors which are explicitly linked to a knowledge resource. Early approaches to sense embeddings adapted existing work to project words and word senses onto a shared distributional space (Iacobacci et al, 2015;Iacobacci and Navigli, 2019), while more recent studies exploited the inner states of pretrained language models (Loureiro and Jorge, 2019;Scarlini et al, 2020a). Instead of modelling language-specific units like words or senses, NASARI (Camacho-Collados et al, 2016) represents language-independent concepts using sparse lexical vectors.…”
Section: Related Workmentioning
confidence: 99%
“…As a result, contextualized word representations have garnered attention (Melamud et al, 2016), enjoying great success in the form of pretrained language models like BERT (Devlin et al, 2019) or XLM (Conneau and Lample, 2019). At the same time, modelling techniques for individual word senses, concepts and named entities have also gained traction (Camacho-Collados et al, 2016;Scarlini et al, 2020a), though their integration into downstream NLP applications is still subject of ongoing investigations (Li and Jurafsky, 2015;.…”
Section: Introductionmentioning
confidence: 99%
“…It is a key task in Natural Language Processing (Navigli 2018), providing semantic information that is potentially beneficial for downstream applications, such as information extraction (Delli Bovi, Espinosa Anke, and Navigli 2015) and machine translation (Pu et al 2018). While much effort has been devoted to building new algorithms or data (Pasini and Navigli 2018;Scarlini, Pasini, and Navigli 2019) for this task, state-ofthe-art systems have yet to break the 80% accuracy ceiling on standard WSD benchmark datasets (Raganato, Delli Bovi, and Navigli 2017;Bevilacqua and Navigli 2019;Vial, Lecouteux, and Schwab 2019;Scarlini, Pasini, and Navigli 2020), showing that the WSD task is far from being solved. Following the literature in the field (Hovy et al 2006;Palmer, Dang, and Fellbaum 2007;Navigli, Litkowski, and Hargraves 2007), we argue that the reason for this unsatisfactory performance does not lie solely in the complexity of the task but also in the fine granularity of the sense inventory adopted, i.e., WordNet (Fellbaum 1998).…”
Section: Introductionmentioning
confidence: 99%